Shadowing Ralph Ellison - Wright, John S. (John Samuel), 1946- (Margaret Walker Alexander series in African American studies., 2006)
In 1952, Ralph Ellison (1914-1994) published his novel Invisible Man, which transformed the dynamics of American literature. The novel won the National Book Award, extended the themes of his early short stories, and dramatized in fictional form the cultural theories expressed in his later essay collections Shadow & Act and Going to the Territory. In Shadowing Ralph Ellison, John Wright traces Ellison's intellectual and aesthetic development and the evolution of his cultural philosophy throughout his long career. The book explores Ellison's published fiction, his criticism and correspondence, a.